Copper-containing silver powder, conductive paste, conductive film, and solar cell

JP7640626B2Active Publication Date: 2025-03-05DOWA ELECTRONICS MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023123738
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-03-05
Estimated Expiration
2043-07-28

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、導電膜のライン抵抗を低減可能な銅含有銀粉を提供できる。 また、本発明によれば、導電膜のライン抵抗を低減可能な導電性ペーストを提供できる。 また、本発明によれば、ライン抵抗が低減された導電膜を提供できる。 また、本発明によれば、優れた性能を有する太陽電池セルを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640626000004
    Figure 0007640626000004
  • Figure 0007640626000005
    Figure 0007640626000005
  • Figure 0007640626000006
    Figure 0007640626000006
Patent Text Reader

Abstract

To provide a copper-containing silver powder capable of reducing line resistance of a conductive film.SOLUTION: The present invention pertains to a copper-containing silver powder. In a differential curve of a TMA curve from 100°C to 600°C obtained by thermomechanical analysis in which the temperature of the copper-containing silver powder is raised at a temperature increase rate of 10°C / min, the copper-containing silver powder has an expansion peak and has, on the lower temperature side from the expansion peak, a first shrinkage peak at which the dTMA is -0.10% / min or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper-containing silver powder, a conductive paste, a conductive film, and a solar cell. [Background technology]

[0002] A method of forming a conductive film for electrodes, electrical wiring, etc., by applying or printing a conductive paste containing a conductive metal powder onto a substrate such as a film, a board, or an electronic component, and then heating the paste to dry, harden, or bake it has been widely used in the past. However, with the recent increase in the performance of electronic devices, the conductive film formed using the conductive paste is required to have lower resistance, and this requirement is becoming stricter every year.

[0003] In response to the above demands, for example, Patent Document 1 proposes the use of a silver powder consisting of a flaky silver powder and a spherical silver powder, in which a polyvalent carboxylic acid is adhered to the surface of at least one of the flaky silver powder and the spherical silver powder, as a conductive metal powder, in order to obtain a conductive paste composition having high conductivity (low resistance). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-100573 A Summary of the Invention [Problem to be solved by the invention]

[0005] Here, for the silver powder (silver powder) that can be used in conventional conductive pastes, there is room for further improvement in terms of reducing the line resistance of the conductive film formed using the conductive paste.

[0006] Therefore, an object of the present invention is to provide a copper-containing silver powder capable of reducing the line resistance of a conductive film. Another object of the present invention is to provide a conductive paste capable of reducing the line resistance of a conductive film. Another object of the present invention is to provide a conductive film with reduced line resistance. Another object of the present invention is to provide a solar cell having excellent performance. [Means for solving the problem]

[0007] As a result of extensive research by the inventors to solve the above-mentioned problems, the inventors have completed the present invention described below.

[0008] That is, the gist of the present invention for solving the above-mentioned problems is as follows.

[0009] [1] A copper-containing silver powder comprising: In the differential curve of the TMA curve from 100 ° C to 600 ° C obtained by thermomechanical analysis in which the copper-containing silver powder is heated at a heating rate of 10 ° C / min, A copper-containing silver powder having an expansion peak and a first shrinkage peak at a temperature lower than the expansion peak, the first shrinkage peak having a dTMA of -0.10% / min or less.

[0010] [2] The copper-containing silver powder according to [1], which has a second shrinkage peak in which dTMA is -0.30% / min or less between the temperature of the expansion peak and 300°C in the differential curve.

[0011] [3] The copper-containing silver powder according to [1] or [2], wherein the differential curve between 300°C and 600°C is meandering.

[0012] [4] A conductive paste comprising the copper-containing silver powder according to [1] or [2], aluminum, and a solvent.

[0013] [5] A conductive film formed by using the conductive paste according to [4].

[0014] [6] A solar cell comprising the conductive film according to [5]. Effect of the Invention

[0015] According to the present invention, it is possible to provide a copper-containing silver powder capable of reducing the line resistance of a conductive film. Moreover, according to the present invention, it is possible to provide a conductive paste capable of reducing the line resistance of a conductive film. Moreover, according to the present invention, it is possible to provide a conductive film with reduced line resistance. Moreover, according to the present invention, a solar cell having excellent performance can be provided. [Brief description of the drawings]

[0016] [Figure 1] 1 is a scanning electron microscope photograph of a cross section of the copper-containing silver powder of Example 1. [Diagram 2] 1 is a dTMA curve of the copper-containing silver powder of Example 1. [Diagram 3] 4 is a dTMA curve of the copper-containing silver powder of Example 2. [Figure 4] 4 is a dTMA curve of the copper-containing silver powder of Example 3. [Diagram 5] 4 is a dTMA curve of the silver powder of Comparative Example 1. [Figure 6] 4 is a dTMA curve of the mixed silver powder of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The copper-containing silver powder of the present invention is suitable for use as a conductive filler for conductive paste. The conductive paste using the copper-containing silver powder of the present invention can be used to form a conductive pattern on a substrate or to form an electrode. The conductive paste using the copper-containing silver powder of the present invention can be printed on a substrate by, for example, screen printing, offset printing, photolithography, or the like to form a conductive film such as a conductive pattern or an electrode.

[0018] In recent years, in solar cells (particularly n-type solar cells) having a silicon substrate and a conductive film such as an electrode or electrical wiring formed on the surface of the silicon substrate, attempts have been made to add aluminum such as aluminum powder to the conductive paste used to form the conductive film in order to reduce the contact resistance (interface resistance) at the interface between the semiconductor layer and the electrode, etc. However, when aluminum is added to the conductive paste, the bulk resistance of the formed conductive film increases, which may result in a problem that the line resistance of the conductive film may increase. The copper-containing silver powder of the present invention can reduce the line resistance of the conductive film, and therefore can be particularly suitably used in solar cells, specifically, in aluminum-containing conductive pastes used to form the conductive film provided in solar cells.

[0019] (Terminology and Measurement Methods) Prior to describing the embodiments, the terms and measurement methods used in this specification will be described.

[0020] <Thermo-mechanical analysis of copper-containing silver powder> Thermomechanical analysis (TMA) of the copper-containing silver powder was carried out as follows. First, 0.3 g of copper-containing silver powder was weighed. Next, the copper-containing silver powder was put into a specified mold with a diameter of 5 mmφ, and pressed with a press machine for 1 minute under a load of 50 kg to prepare a disk-shaped measurement sample. This measurement sample was set in the sample holder of a thermomechanical analysis (TMA) device (Thermo plus EVO 2 series TMA8311), and a measurement load of 98 mN was applied by the measurement probe, and the temperature was raised from 25°C to 900°C at a heating rate of 10°C / min to measure the expansion rate and contraction rate of the measurement sample. The following evaluations were made on the measurement results from 100°C to 600°C. The expansion rate and contraction rate, as well as the temperature at that time, were recorded every second from the start of the measurement (heating), and a TMA curve was obtained. The obtained TMA curve was differentiated with respect to time to obtain a differential curve of the TMA curve (hereinafter, the differential curve of the TMA curve may be referred to as a "dTMA curve"). Then, using the obtained dTMA curve, the temperature and dTMA of the expansion peak, the temperature and dTMA of the first contraction peak, the temperature and dTMA of the second contraction peak, and the presence or absence of meandering of the dTMA curve between 300°C and 600°C were confirmed. The first contraction peak, the expansion peak, and the second contraction peak are present between 100°C and 300°C. In this specification, the term "expansion peak" refers to a peak having a dTMA of 0.1% / min or more among the upwardly convex peaks in the dTMA curve, and is usually the peak having the maximum dTMA in the dTMA curve. In this specification, the term "meandering" of a dTMA curve refers to a state in which the dTMA curve has multiple valleys or peaks, rather than having 0 to 1 valley (a downwardly convex curve) or peak (an upwardly convex curve).

[0021] <Confirmation of the presence or absence of voids inside silver particles in copper-containing silver powder> In this specification, the presence or absence of voids was confirmed by observing silver particles using the following method. First, the copper-containing silver powder was put into a resin and a hardener, and the resin was solidified. The solidified resin was then cut. The cut surfaces were then polished with a cross-section polisher to expose the cross sections of the silver particles. Each silver particle was then observed with a scanning electron microscope to confirm the presence or absence of voids inside the silver particles. As the resin and hardener, for example, "Epofix Resin" and "Epofix Hardener" manufactured by Struers can be used. As the cross-section polisher, for example, "ArBlade5000" manufactured by Japan High-Technologies Corporation can be used. As the scanning electron microscope, for example, "JSM-IT800SHL" manufactured by JEOL Ltd. can be used. In this specification, the "voids inside the silver particles" do not refer to the spaces created by the irregularities on the surface of the silver particles, but rather to the closed spaces inside the silver particles. In this specification, silver particles having voids therein may be referred to as "void-containing silver particles".

[0022] As used herein, "void diameter (i.e., the diameter of the enclosed space inside a void-containing silver particle)" refers to the diameter of the smallest circle drawn in a scanning electron microscope image that will contain all of the voids. In this specification, a void is a void having a diameter of 15 nm or more when observed using an image of the cross section of a silver particle photographed at 10,000 to 40,000 magnification using the above method.

[0023] <Measurement of copper content in copper-containing silver powder> The amount of copper in the copper-containing silver powder was determined by the following analytical method. 1) 1 g of sample was precisely weighed, 15 mL of pure water and 10 mL of nitric acid (for precision analysis) were added, and the sample was heated at 200°C for 30 minutes. 2) After allowing the sample heated in 1) to cool, the volume was adjusted to 100 mL using pure water, 5 mL of the supernatant was removed, and the volume was adjusted again to 100 mL using pure water to prepare a sample for ICP analysis. 3) The copper standard solution used to create the calibration curve was prepared by adjusting the silver concentration using 5N silver to the same level as the sample for ICP analysis. 4) ICP quantification was performed using an Aglent 5800 ICP-OES from Agilent Technologies.

[0024] <Carbon content, oxygen content, and nitrogen content in copper-containing silver powder> In this specification, the "carbon content" was measured using a carbon / sulfur analyzer (EMIA-810W manufactured by Horiba, Ltd.) at 1350°C in an oxygen stream. The "oxygen content" and "nitrogen content" were measured using an oxygen / nitrogen / hydrogen simultaneous analyzer (ONH836 manufactured by LECO) at an impulse furnace power value of 3500 W in an Ar gas atmosphere.

[0025] <True density of copper-containing silver powder> In this specification, the "true density of copper-containing silver powder" means the density of copper-containing silver powder taking into account the voids present inside the silver particles (i.e., the "closed space inside the silver particles" described above). And in this specification, the method for measuring the true density of copper-containing silver powder was measured by a dry automatic densitometer (also referred to as a true density measuring device) using helium gas. Specifically, the volume of the copper-containing silver powder was measured from the gas volume when the container was filled with helium gas until a constant pressure was reached inside the container, and it was calculated by dividing the mass of the copper-containing silver powder by that volume. At this time, the helium gas can reach the spaces of the unevenness on the particle surface and the spaces between particles, but it cannot reach the closed spaces (i.e., voids) inside the particles that are not in communication with the outside. Therefore, generally, the greater the proportion of voids inside the silver particles, the smaller the true density of the copper-containing silver powder tends to be.

[0026] <Average particle diameter (SEM average particle diameter)> The average particle diameter (SEM average particle diameter) was measured as the average value of the Heywood diameters for 100 or more particles whose outer shapes could all be recognized using the image processing software Mac-View (Ver. 4) manufactured by MOUNTECH in an SEM image with a magnification of 5,000 times.

[0027] <BET specific surface area> In this specification, the "BET specific surface area" was measured by the BET one-point method by nitrogen adsorption using Macsorb HM-model 1210 (manufactured by MOUNTECH). In the measurement of the BET specific surface area, the degassing conditions before measurement were 60 °C for 10 minutes.

[0028] <Particle size distribution> In this specification, the minimum particle diameter (D MIN ), cumulative 10% particle diameter (D 10 ), cumulative 50% particle diameter (D 50 ), cumulative 90% particle diameter (D 90 ), and cumulative 95% particle diameter (D 95 ), and the particle diameter (D MAX) was measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT-3300 EXII, manufactured by Microtrack Bell Corporation).

[0029] <Measurement of copper content in conductive paste> The amount of copper in the conductive paste was determined by the following analytical method. 1) 1 g of the paste was precisely weighed, washed with acetone, and then dried to obtain a sample. 2) 15 mL of pure water and 10 mL of nitric acid (for precision analysis) were added to the dried sample and heated at 200°C for 30 minutes. 3) After allowing the sample heated in 2) to cool, the volume was adjusted to 100 mL using pure water, 5 mL of the supernatant was removed, and the volume was adjusted to 100 mL again using pure water to prepare a sample for ICP analysis. 4) The copper standard solution used to create the calibration curve was prepared by adjusting the silver concentration using 5N silver to the same level as the sample for ICP analysis. 5) ICP volumetric analysis was performed using an Agilent 5800 ICP-ES (Agilent Technologies).

[0030] <Measurement of silver content in conductive paste> The amount of silver in the conductive paste was determined by the following analytical method. 1) 1 g of the paste was precisely weighed, washed with acetone, and then dried to obtain a sample. 2) After drying, 15 mL of pure water and 10 mL of nitric acid (for precision analysis) were added to the sample, and the sample was heated at 200°C for 30 minutes. 3) 15 mL of pure water and 10 mL of hydrochloric acid (for precision analysis) were added to the sample heated in 2) and heated at 150°C for 30 minutes. 4) The silver chloride produced in 3) was aged for more than 12 hours. 5) The silver chloride was filtered through a precisely weighed glass filter and washed with pure water. 6) The glass filter containing silver chloride was dried in a dryer at 120°C for approximately 3 hours until it reached a constant weight. 7) After cooling in the desiccator for at least 1 hour, the glass filter containing silver chloride was precisely weighed and the silver content was calculated from the mass of silver chloride produced.

[0031] (Silver powder containing copper) The copper-containing silver powder of the present invention has an expansion peak and a first contraction peak on the lower temperature side of the expansion peak, with dTMA of -0.10% / min or less (absolute value of 0.10% / min or more in the negative direction) in a dTMA curve from 100°C to 600°C obtained by thermomechanical analysis in which the copper-containing silver powder is heated at a heating rate of 10°C / min. The above-mentioned copper-containing silver powder can reduce the line resistance of the conductive film. In particular, the effect of reducing bulk resistance is remarkable in the aluminum-containing conductive paste. The reason for this is that the conductive film formed using the conductive paste is usually a film formed by applying or printing the conductive paste and firing it. When the copper-containing silver powder used in the conductive paste shrinks at a certain rate at a temperature before it expands, gaps are formed between the silver particles, and the presence of these gaps makes it easier for gas components in the gaps to escape outside the conductive paste, so that the excessive expansion of the conductive paste itself due to subsequent firing is effectively suppressed, and the resulting conductive film becomes dense, which is presumably why the bulk resistance of the conductive film can be effectively reduced.

[0032] In the dTMA curve, the dTMA of the first contraction peak is −0.10% / min or less, preferably −0.30% / min or less, more preferably −0.50% / min or less, and even more preferably −0.80% / min or less. If the dTMA of the first shrinkage peak is −0.10% / min or less, the line resistance of the conductive film can be effectively reduced. On the other hand, the dTMA of the first contraction peak is, for example, −3.00% / min or more, may be −2.00% / min or more, or may be −1.50% / min or more.

[0033] In the dTMA curve, the temperature of the first contraction peak is not particularly limited as long as it is lower than the temperature of the expansion peak, and may be, for example, 150°C or more, 170°C or more, or 180°C or more, or may be, for example, 210°C or less, 200°C or less, 195°C or less, or 190°C or less.

[0034] In the dTMA curve, the dTMA of the expansion peak is 0.1% / min or more, preferably 0.50% / min or more, more preferably 1.00% / min or more, even more preferably 2.00% / min or more, and even more preferably 3.00% / min or more. If the dTMA of the expansion peak is 0.1% / min or more, the line resistance of the conductive film can be effectively reduced. On the other hand, the dTMA of the expansion peak is, for example, 10.00% / min or less, and may be 5.00% / min or less.

[0035] In the dTMA curve, the temperature of the expansion peak is not particularly limited as long as it is higher than the temperature of the first contraction peak, but may be, for example, 200°C or more, or 210°C or more, or may be, for example, 270°C or less, or 250°C or less.

[0036] The difference between the dTMA of the expansion peak and the dTMA of the first contraction peak ("dTMA of the expansion peak" - "dTMA of the first contraction peak") is not particularly limited as long as each dTMA satisfies the above requirements, but is preferably 0.50% / min or more, more preferably 2.00% / min or more, and even more preferably 3.50% / min or more. If the difference between the dTMA of the expansion peak and the dTMA of the first contraction peak is 0.50% / min or more, the line resistance of the conductive film can be effectively reduced. On the other hand, the difference between the dTMA of the expansion peak and the dTMA of the first contraction peak is, for example, 10.00% / min or less, and may be 7.00% / min or less.

[0037] The difference between the temperature of the expansion peak and the temperature of the first shrinkage peak ("temperature of the expansion peak" - "temperature of the first shrinkage peak") is not particularly limited as long as it satisfies the relationship "temperature of the expansion peak" > "temperature of the shrinkage peak", but is preferably 3°C or more, more preferably 10°C or more, even more preferably 20°C or more, and even more preferably 30°C or more. If the difference between the temperature of the expansion peak and the temperature of the first contraction peak is 3° C. or more, the line resistance of the conductive film can be effectively reduced. On the other hand, the difference between the temperature of the expansion peak and the temperature of the first contraction peak is, for example, 70°C or less, and may be 50°C or less.

[0038] The copper-containing silver powder of the present invention preferably has a second contraction peak in the dTMA curve, with dTMA of -0.30% / min or less (absolute value of 0.30% / min or more in the negative direction from zero) between the expansion peak temperature and 300° C. If the copper-containing silver powder has a second contraction peak, the line resistance of the conductive film can be effectively reduced. Here, the dTMA of the second contraction peak is not particularly limited as long as it is −0.30% / min or less, but is preferably −0.50% / min or less. On the other hand, the dTMA of the second contraction peak is, for example, −3.00% / min or more, may be −2.00% / min or more, or may be −1.50% / min or more.

[0039] The difference between the dTMA of the expansion peak and the dTMA of the second contraction peak ("dTMA of the expansion peak" - "dTMA of the second contraction peak") is not particularly limited as long as each dTMA satisfies the above requirements, but is preferably 0.50% / min or more, more preferably 2.00% / min or more, and even more preferably 3.50% / min or more. If the difference between the dTMA of the expansion peak and the dTMA of the second contraction peak is 0.50% / min or more, the line resistance of the conductive film can be effectively reduced. On the other hand, the difference between the dTMA of the expansion peak and the dTMA of the second contraction peak is, for example, 10.00% or less, and may be 7.00% / min or less.

[0040] The copper-containing silver powder of the present invention preferably has a meandering dTMA curve between 300°C and 600°C. Such copper-containing silver powder can effectively reduce the line resistance of the conductive film. In conventional silver powders, after the above-mentioned contraction peak or expansion peak occurs (at 300°C or higher), only gentle valleys and peaks occur in the dTMA curve, but the copper-containing silver powder of the present invention has a meandering dTMA curve at 300°C or higher. In the conductive paste, glass can soften at 500 to 600°C and aluminum powder can melt at 500 to 650°C, so it is considered that an interaction occurs when the copper-containing silver powder, which has a meandering dTMA curve at a temperature of 300°C or higher, coexists with glass and aluminum powder in the conductive paste.

[0041] The copper content in the copper-containing silver powder means the mass ratio of copper to the total mass of silver and copper in the copper-containing silver powder. The copper content in the copper-containing silver powder is preferably 10 ppm or more, more preferably 30 ppm or more, and is preferably 10,000 ppm or less, more preferably 3,000 ppm or less, even more preferably 1,000 ppm or less, and even more preferably 100 ppm or less. If the copper content in the copper-containing silver powder is 10 ppm or more, the bulk resistance of the conductive film can be effectively reduced. On the other hand, if the copper content in the copper-containing silver powder is 10,000 ppm or less, it is possible to relatively increase the silver content in the copper-containing silver powder, and as a result, the line resistance of the conductive film can be effectively reduced.

[0042] The carbon content in the copper-containing silver powder means the mass ratio of carbon to the total mass of the copper-containing silver powder. The carbon content in the copper-containing silver powder is, for example, 0.06 mass% or more, may be 0.2 mass% or more, or 0.3 mass% or more, for example, 1 mass% or less, may be 0.7 mass% or less, or may be 0.5 mass% or less.

[0043] The oxygen content in the copper-containing silver powder means the mass ratio of oxygen to the total mass of the copper-containing silver powder. The oxygen content in the copper-containing silver powder is, for example, 0.11 mass% or more, may be 0.2 mass% or more, or 0.3 mass% or more, for example, 1 mass% or less, may be 0.8 mass% or less, or may be 0.6 mass% or less.

[0044] The nitrogen content in the copper-containing silver powder means the mass ratio of nitrogen to the total mass of the copper-containing silver powder. The nitrogen content in the copper-containing silver powder is, for example, 0.01 mass% or more, may be 0.06 mass% or more, or 0.09 mass% or more, for example, 0.5 mass% or less, may be 0.3 mass% or less, or may be 0.2 mass% or less.

[0045] The true density of copper-containing silver powder is 10 g / cm 3 It is preferable that the density is 9.8 g / cm or less. 3 More preferably, it is 9.7 g / cm or less. 3 It is even more preferable that: The true density of copper-containing silver powder is 10g / cm 3 If it is equal to or less than this, the line resistance of the conductive film can be effectively reduced. On the other hand, the true density of copper-containing silver powder is, for example, 9 g / cm 3 More than 9.2g / cm 3 More than 9.4g / cm 3 More than that is fine.

[0046] The minimum particle size of the copper-containing silver powder based on volume (D MIN ) is, for example, 0.05 μm or more, may be 0.1 μm or more, or may be 0.2 μm or more, for example, 1 μm or less, may be 0.7 μm or less, or may be 0.5 μm or less.

[0047] Cumulative 10% particle size (D 10 ) is, for example, 0.1 μm or more, may be 0.5 μm or more, or may be 0.8 μm or more, and is, for example, 2 μm or less, may be 1.5 μm or less, or may be 1.2 μm or less.

[0048] Cumulative 50% particle size (D 50 ) is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 1.5 μm or more, and is preferably 6 μm or less, more preferably 2.5 μm or less, and even more preferably 1.9 μm or less. D 50 If is within the above range, the line resistance of the conductive film can be effectively reduced.

[0049] Cumulative 90% particle size (D 90 ) is, for example, 1.5 μm or more, may be 2 μm or more, or may be 2.5 μm or more, and is, for example, 5 μm or less, may be 4 μm or less, or may be 3.5 μm or less.

[0050] Cumulative 95% particle size (D 95 ) is, for example, 2 μm or more, may be 2.3 μm or more, or may be 3 μm or more, and is, for example, 10 μm or less, may be 7 μm or less, or may be 4 μm or less.

[0051] Cumulative 100% (i.e., maximum particle) particle diameter (D MAX ) is, for example, 3 μm or more, may be 4 μm or more, or may be 5 μm or more, for example, 15 μm or less, may be 10 μm or less, or may be 8 μm or less.

[0052] The BET specific surface area of ​​copper-containing silver powder is 0.1 m 2 / g or more, and 0.3m 2 / g or more is more preferable, and 0.45m 2 / g or more is more preferable, 2 / g or less, and 0.8m 2 / g or less is more preferable, and 0.6m 2 It is more preferable that the molecular weight is not more than 1 / g. When the BET specific surface area of ​​the copper-containing silver powder is within the above range, the line resistance of the conductive film can be effectively reduced.

[0053] In one embodiment, the copper-containing silver powder of the present invention contains void-containing silver particles, and may optionally contain silver particles that do not have voids therein. In addition, when the copper-containing silver powder of the present invention is observed in cross section, it is preferable that the void-containing silver particles account for more than half of the total silver particles.

[0054] <Silver particles containing voids> The void-containing silver particles that can be contained in the copper-containing silver powder of the present invention are silver particles having voids therein, and preferably contain copper. Incidentally, as a method for confirming that the void-containing silver particles contain copper, for example, EDS, XPS, etc. can be used.

[0055] In the void-containing silver particles, the average void diameter is determined by measuring the diameter of voids of 15 nm or more contained in at least 10 silver particle cross sections in the particle cross section images of 10,000 to 40,000 times magnification. The average void diameter is, for example, 30 nm or more, or may be 50 nm or more, or 100 nm or more, or, for example, 500 nm or less, or may be 300 nm or less, or may be 200 nm or less.

[0056] When the void-containing silver particles contain copper, the content of silver particles made of silver is preferably small from the viewpoint of suppressing uneven distribution of copper in the conductive paste. The content of silver particles made of silver in the copper-containing silver powder means the mass ratio of silver particles made of silver to the total mass of the copper-containing silver powder. The content of silver particles made of silver in the copper-containing silver powder is, for example, 50 mass% or less, may be 20 mass% or less, may be 10 mass% or less, or may be 0 mass%, that is, the copper-containing silver powder may not contain silver particles made of silver.

[0057] <Method of manufacturing copper-containing silver powder> The copper-containing silver powder of the present invention can be produced, without being particularly limited thereto, by a method including, for example, a reduction step in which a reducing agent is added to a mixed solution containing a silver compound and the above-mentioned copper-containing compound (e.g., a copper compound, etc.) to precipitate void-containing silver particles, and a separation step in which the void-containing silver particles are separated from the mixed solution and dried to obtain the copper-containing silver powder. In addition, in addition to the reduction step and the separation step, the above-mentioned manufacturing method may further include a surface treatment agent addition step in which a surface treatment agent is added to the mixed liquid containing the void-containing silver particles obtained in the reduction step to obtain surface-treated void-containing silver particles.

[0058] An example of a method for producing copper-containing silver powder will be described below, but the method for producing copper-containing silver powder is not limited thereto.

[0059] [Reduction step] In the reduction step, a reducing agent is added to a mixture containing a silver compound and a copper compound to precipitate void-containing silver particles. The mixture is usually an aqueous solution or suspension containing a silver compound and a copper compound, and contains water as a solvent. The mixture containing a silver compound and a copper compound may optionally contain a pH adjuster or the like. The mixture obtained after the void-containing silver particles have been precipitated is usually a suspension (so-called slurry) or dispersion in which the void-containing silver particles are dispersed.

[0060] The reducing agent added to the mixture in the reduction step preferably contains a compound having an aldehyde group. By using a reducing agent containing a compound having an aldehyde group, void-containing silver particles can be obtained efficiently. Examples of such reducing agents include an aqueous formaldehyde solution (so-called formalin) and an aqueous acetaldehyde solution, and it is preferable to use formalin because it can more efficiently obtain void-containing silver particles. In addition, from the viewpoint of effectively generating voids, ultrasonic waves or the like may be used during reduction precipitation.

[0061] The silver compound is not particularly limited, and examples thereof include silver nitrate, silver oxide, etc. In addition, it is preferable to use, as the silver compound, a silver ammine complex obtained by reacting silver nitrate or silver oxide with ammonia water or an ammonium salt.

[0062] The copper compound is not particularly limited, and examples thereof include copper(II) nitrate trihydrate, copper oxide, etc. In addition, it is preferable to use, as the copper compound, a copper ammine complex obtained by reacting copper(II) nitrate trihydrate or copper oxide with ammonia water or an ammonium salt.

[0063] In the mixed liquid, the ratio of copper to silver is preferably 0.001% by mass or more, preferably 0.003% by mass or more, preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, and even more preferably 0.01% by mass or less. If the ratio of copper to silver is 0.001 mass % or more, the bulk resistance of the conductive film can be effectively reduced. On the other hand, if the ratio of copper to silver is 3 mass % or less, it is possible to relatively increase the ratio of silver, and as a result, the line resistance of the conductive film can be effectively reduced.

[0064] The pH adjuster that the mixed solution may contain may be a common acid or base, such as nitric acid, sodium hydroxide, etc. In the reduction step, it is preferable to adjust the mixed solution to be alkaline.

[0065] [Surface treatment agent addition step] In the optional surface treatment agent addition step, a surface treatment agent is added to the mixed liquid containing the void-containing silver particles obtained in the reduction step to obtain surface-treated void-containing silver particles (hereinafter sometimes referred to as "surface-treated void-containing silver particles"). The mixed liquid containing the surface-treated void-containing silver particles is usually a suspension (so-called slurry) or a dispersion in which the surface-treated void-containing silver particles are dispersed.

[0066] Examples of surface treatment agents include behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, ricinoleic acid, oleic acid, linoleic acid, linolenic acid, benzotriazole, etc. These may be used alone or in combination of two or more.

[0067] The amount of the surface treatment agent added in the surface treatment agent adding step is usually 0.05% by mass or more and 0.5% by mass or less based on the mass of silver contained in the mixed liquid obtained in the reduction step.

[0068] The amount of surface treatment agent that adheres to the surface-treated void-containing silver particles by the surface treatment agent addition process and remains after the separation process is a value measured on the copper-containing silver powder after the separation process described below, with the type of surface treatment agent specified. The type of the surface treatment agent can be identified by qualitative analysis by gas chromatography of the surface treatment agent volatilized by heating the copper-containing silver powder.

[0069] The amount of the surface treatment agent attached to the copper-containing silver powder can be determined according to the quantitative analysis method for fatty acids described in Japanese Patent No. 5,622,543. Specifically, first, the copper-containing silver powder is dissolved in an acid, and then an organic solvent is mixed therein. The entire amount of the surface treatment agent is extracted into the organic solvent phase. A predetermined amount of the organic solvent phase is then separated and evaporated to dryness. The carbon content of the remaining solid matter is measured using a carbon-sulfur analyzer, and the carbon content can be calculated.

[0070] For example, if the surface treatment agent is specified to be stearic acid and no carbon source other than stearic acid is contained in the copper-containing silver powder, the method for measuring stearic acid is as follows.

[0071] When the carbon amount (strength) of each of the standard solutions with different stearic acid contents (mg) is measured by a carbon-sulfur analyzer to obtain a calibration curve, the slope of the curve is A (strength / mg). The mass X (mg) and concentration Y (%) of stearic acid in the copper-containing silver powder can be calculated by the following formulas (A) and (B), respectively, by taking a predetermined amount b (mL) from the treatment agent extracted into the total organic solvent amount a (mL) by the treatment of the copper-containing silver powder, measuring the amount of carbon obtained by measuring the remaining solid matter, and taking C (strength), and taking M (g) as the amount of copper-containing silver powder dissolved in acid. X(mg) = (C / A × a / b) (A) Y(%)=X / (M×1000)×100...(B)

[0072] When oleic acid is used as a treatment agent, the carbon content is measured and calculated in the same manner as above. The oleic acid concentration is also calculated using the calibration curve of stearic acid. The molecular weight of stearic acid is 284.48, with a carbon content of 216.19, and the molecular weight of oleic acid is 282.46, with a carbon content of 216.19, so the oleic acid concentration Y' can be calculated using the following formula (C). Oleic acid concentration Y' (%) = Y × (216.19 / 284.48) × (282.46 / 216.19) (C)

[0073] The amount of the surface treatment agent adhered is usually 0.05% by mass or more and 0.5% by mass or less based on the mass of the copper-containing silver powder.

[0074] [Separation process] In the separation step, the void-containing silver particles or the surface-treated void-containing silver particles (hereinafter, collectively referred to as "void-containing silver particles, etc.") are separated from the mixed liquid and dried to obtain a copper-containing silver powder. The copper-containing silver powder obtained in the separation step can be the copper-containing silver powder of the present invention. In addition, the separation step may optionally include a washing and recovery step of recovering and washing the separated void-containing silver particles and the like.

[0075] In the washing and recovery step, for example, the aggregate of the separated void-containing silver particles, etc. is formed into a cake-like form, and the cake of the aggregate of the void-containing silver particles, etc. is washed. The washing in the washing and recovery step may be performed using, for example, pure water. The dehydration in the washing and recovery step may be performed, for example, by decantation or a filter press. The end point of the washing may be determined using the electrical conductivity of the washing water. Specifically, the end of the washing may be determined when the electrical conductivity of the washing water becomes equal to or lower than a predetermined value. The void-containing silver particles, etc. after washing may be subjected to a drying step in an aggregated state such as a cake-like form.

[0076] In the drying step, the aggregate of void-containing silver particles and the like that contains moisture and is in an aggregated state is dried. The drying step may be performed by vacuum drying or an airflow type dryer. In the drying step, the aggregate of void-containing silver particles and the like may be blown with a high-pressure air flow, or the cake or the copper-containing silver powder in the drying process may be put into a stirrer having a stirring rotor and stirred, thereby giving a dispersing force to the cake or the copper-containing silver powder in the dried void-containing state, and an operation may be performed to promote dispersion or drying.

[0077] In the drying step, the temperature of the copper-containing silver powder is usually 100° C. or less. If the temperature of the copper-containing silver powder is 100° C. or less, sintering of void-containing silver particles and the like in the copper-containing silver powder can be effectively suppressed.

[0078] Since the copper-containing silver powder after drying may be in the form of lumps, a dry crushing treatment or classification operation may be performed simultaneously with or after the drying step in order to improve the handleability of the copper-containing silver powder. Here, improving the handleability of the copper-containing silver powder means, for example, ensuring a degree of fluidity that does not interfere with the supply operation into the device, or moderately loosening the copper-containing silver powder so that the processing in the device proceeds efficiently.

[0079] The method of the dry crushing treatment is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable to use a crusher that rotates a stirring blade to crush and fluidize the copper-containing silver powder, and for example, a Henschel mixer, a sample mill, a blender, a coffee mill, etc. can be used.

[0080] (Conductive paste) The conductive paste of the present invention contains the above-mentioned copper-containing silver powder of the present invention, aluminum, and a solvent. Since the conductive paste of the present invention contains the copper-containing silver powder of the present invention, the line resistance of the conductive film can be reduced.

[0081] Here, the silver content in the conductive paste means the mass ratio of silver to the total mass of all components in the conductive paste. The silver content in the conductive paste is preferably 50 mass% or more, more preferably 80 mass% or more, and is preferably 98 mass% or less, more preferably 95 mass% or less.

[0082] The copper content in the conductive paste means the mass ratio of copper to the total mass of all components in the conductive paste. The copper content in the conductive paste is preferably 5 ppm or more, and more preferably 10 ppm or more. The copper content in the conductive paste is preferably 5000 ppm or less, more preferably 500 ppm or less, and even more preferably 100 ppm or less. If the copper content in the conductive paste is within the above range, the line resistance of the conductive film can be effectively reduced.

[0083] <Filler> The conductive paste may contain a portion of silver powder that does not contain copper. Hereinafter, the copper-containing silver powder and the copper-free silver powder may be collectively referred to as a filler.

[0084] The content of the filler in the conductive paste means the mass ratio of the filler to the total mass of all components in the conductive paste. The content of the filler in the conductive paste is preferably 50 mass% or more, more preferably 80 mass% or more, and is preferably 98 mass% or less, more preferably 95 mass% or less. In addition, in the conductive paste, since this can suppress the uneven distribution of copper caused by the filler, it is preferable that the proportion of the copper-containing silver powder of the present invention in the filler is high, preferably 50 mass% or more, and most preferably 100 mass%.

[0085] The copper content in the filler means the mass ratio of copper to the total mass of silver and copper in the filler. The copper content in the filler is preferably 5 ppm or more, and more preferably 10 ppm or more. The copper content in the filler is 10,000 ppm or less, preferably 5,000 ppm or less, more preferably 500 ppm or less, and even more preferably 100 ppm or less. If the copper content in the filler is within the above range, the line resistance of the conductive film can be effectively reduced.

[0086] <Aluminum> The aluminum contained in the conductive paste of the present invention may be either metallic aluminum or an aluminum compound, but is preferably metallic aluminum. Examples of the form of metallic aluminum include aluminum (metallic aluminum) and an aluminum alloy. Here, in the conductive paste, the aluminum is preferably in the form of powder, and examples of the powder include aluminum powder (powder made of metallic aluminum), aluminum alloy powder, silver-coated aluminum powder, aluminum-adhered silver powder, etc. As the aluminum, it is particularly preferable to use aluminum powder. In addition, since the aluminum powder is a powder made of metallic aluminum, it does not contain any components other than impurities (e.g., iron, silicon, etc.) that are inevitably mixed in during production. The content of metallic aluminum in the aluminum powder is usually 99 mass% or more, preferably 99.5 mass% or more, and more preferably 99.8 mass% or more. The surfaces of the aluminum powder, aluminum alloy powder, silver-coated aluminum powder, aluminum-adhered silver powder, etc. may be oxidized. For example, the aluminum powder may have an aluminum oxide film on the surface.

[0087] When the aluminum is in the form of powder, the average diameter (SEM average diameter) of the powder is preferably 3.0 μm or less, and more preferably 2.0 μm or less. If the average diameter (SEM average diameter) of the powdered aluminum is 3.0 μm or less, the conductive paste can be suitably used for forming a thin conductive film.

[0088] The aluminum content in the conductive paste means the mass ratio of aluminum to the total mass of all components in the conductive paste. The aluminum content in the conductive paste is, for example, 0.1 mass% or more, 0.5 mass% or more, or 1 mass% or more, for example, 5 mass% or less, 3 mass% or less, or 2 mass% or less.

[0089] <Solvent> The solvent (i.e., dispersion medium) of the conductive paste is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include texanol, butyl carbitol acetate, tributyl citrate, 1-octanol, terpineol, butyl carbitol, etc. These may be used alone or in combination of two or more.

[0090] The content of the solvent in the conductive paste means the mass ratio of the solvent to the total mass of all components in the conductive paste. The content of the solvent in the conductive paste is preferably 1 mass% or more and 19 mass% or less.

[0091] <Other ingredients> The conductive paste may further contain components other than the above-mentioned copper-containing silver powder, aluminum, solvent, and any copper-free silver powder (hereinafter, sometimes referred to as "other components"). Other components that may be optionally contained in the conductive paste include, for example, glass frit, binder, dispersant, viscosity modifier, etc. These may be used alone or in combination of two or more.

[0092] The glass frit is a component that can improve the adhesion between the conductive film obtained by firing the conductive paste and the substrate. The glass frit can be appropriately selected according to the purpose, and can be used without any particular limitation as long as it is generally usable for solar cells, etc., but it is preferable that the glass frit contains components such as Si, B, Al, Bi, Li, Na, Mg, Pb, Zn, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu, Ba, and Cr. Such components can be present in the glass frit in the form of oxides, compounds that generate oxides when heated, other compounds, and mixtures thereof.

[0093] The content of the glass frit in the conductive paste means the mass ratio of the glass frit to the total mass of all components in the conductive paste. The content of the glass frit in the conductive paste is preferably 0.1 mass% or more and 10 mass% or less. Here, preferred oxides are alkali metal oxides, alkaline earth metal oxides, rare earth oxides, Group 14 to Group 16 oxides, other oxides, or combinations thereof. The glass frit is usually in the form of glass powder.

[0094] Examples of the binder include epoxy resins, acrylic resins, polyester resins, polyimide resins, polyurethane resins, phenoxy resins, silicone resins, cellulose, etc. These may be used alone or in combination of two or more.

[0095] Examples of dispersants include oleic acid, triacetin, stearic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, linolenic acid, etc. These may be used alone or in combination of two or more.

[0096] Examples of the viscosity modifier include methylphenylpolysiloxane, hydrogenated castor oil, and fatty acid amides.

[0097] <Conductive paste properties> The viscosity of the conductive paste is not particularly limited and can be selected appropriately depending on the purpose, but under conditions of a paste temperature of 25°C and a rotation speed of 1 rpm, it is preferably 150 Pa·s or more, more preferably 200 Pa·s or more, and is preferably 800 Pa·s or less, and more preferably 750 Pa·s or less. If the viscosity of the conductive paste is 150 Pa·s or more, printing defects such as "bleeding" and "printing sagging" that can occur when forming a conductive film by printing or other methods can be effectively suppressed. On the other hand, if the viscosity of the conductive paste is 800 Pa·s or less, breakage in the resulting conductive film can be effectively prevented, making it possible to form a thinner conductive film.

[0098] <Applications of conductive paste> The conductive paste of the present invention is suitable for forming a conductive film, that is, for forming a conductive pattern on a substrate or for forming an electrode. For example, it can be applied directly to various substrates such as silicon wafers for solar cells, films for touch panels, and glass for EL devices, or can be applied or printed on a substrate on which a transparent conductive film is further provided as required, to form a conductive film. The conductive film formed using the conductive paste of the present invention can be suitably used for electrodes or electrical wiring applications such as collector electrodes for solar cells, external electrodes for chip-type electronic components, RFID, electromagnetic shields, vibrator bonding, membrane switches, and electroluminescence.

[0099] <Method of manufacturing conductive paste> The method for producing the conductive paste of the present invention is not particularly limited, and can be obtained, for example, by mixing each material that can be contained in the conductive paste described above, and dispersing and / or kneading the resulting mixture. For dispersion and kneading, for example, ultrasonic dispersion, a disperser, a three-roll mill, a ball mill, a bead mill, a two-axis kneader, a self-revolving mixer, etc. can be used.

[0100] (Conductive film) The conductive film of the present invention is formed by using the conductive paste of the present invention described above. Since the conductive film of the present invention is formed by using the conductive paste of the present invention described above, the line resistance is reduced. The conductive film of the present invention is usually a film formed by applying or printing the above-mentioned conductive paste of the present invention onto a substrate or the like, and then baking the same.

[0101] (Solar cell) The solar cell of the present invention includes the conductive film of the present invention described above. The solar cell of the present invention has excellent performance because it includes a conductive film with reduced line resistance. The conductive film included in the solar cell can function as an electrode (collecting electrode, etc.) or electrical wiring of the solar cell. The conductive film provided in the solar cell of the present invention is usually a film formed by applying or printing the above-mentioned conductive paste of the present invention onto a substrate or the like, and then firing the same.

[0102] The solar cell of the present invention is not particularly limited as long as it comprises the conductive film of the present invention, and may appropriately comprise a semiconductor substrate, a diffusion layer, an anti-reflection layer, a BSF (Back Surface Field) layer, a front electrode, a back electrode, etc. EXAMPLES

[0103] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples in any way.

[0104] (Preparation of Silver Powder X1) 40.8 g of a 5% by mass aqueous solution of copper (II) nitrate trihydrate was added to 3.5 L of an aqueous solution of silver nitrate containing 0.14 mol / L silver ions, to obtain a mixed solution containing silver nitrate and copper (II) nitrate trihydrate (1% by mass of copper relative to silver). Next, while stirring the mixed solution, 113.2 g of 28% by mass ammonia water was added, and the liquid temperature of the mixed solution was adjusted to 45°C. Next, 15 g of a 20% by mass aqueous solution of sodium hydroxide was added to the mixed solution to adjust the pH, and 250 g of a 26% by mass aqueous solution of formaldehyde was added as a reducing agent to precipitate void-containing silver particles. Next, 15 seconds after adding the reducing agent to the mixed solution, a 0.18% by mass isopropanol solution containing stearic acid relative to silver was added. Stirring was stopped, and the solid matter was filtered using a Nutsche filter and washed with water, and the obtained solid matter was dried in a vacuum dryer at 73°C for 10 hours. After drying, the mixture was subjected to a dry crushing process using a sample mill to obtain a copper-containing silver powder, Silver Powder X1.

[0105] [Measurement of copper content in silver powder X1] The copper content in the silver powder X1 was quantified by the following analytical method. 1) 1 g of sample was precisely weighed, 15 mL of pure water and 10 mL of nitric acid (for precision analysis) were added, and the sample was heated at 200°C for 30 minutes. 2) After allowing the sample heated in 1) to cool, the volume was adjusted to 100 mL using pure water, 5 mL of the supernatant was removed, and the volume was adjusted again to 100 mL using pure water to prepare a sample for ICP analysis. 3) The copper standard solution used to create the calibration curve was prepared by adjusting the silver concentration using 5N silver to the same level as the sample for ICP analysis. 4) ICP quantification was performed using an Aglent 5800 ICP-OES from Agilent Technologies.

[0106] [Measurement of carbon, oxygen and nitrogen content] The carbon content was measured using a carbon and sulfur analyzer (EMIA-810W, manufactured by Horiba, Ltd.). The oxygen and nitrogen content was measured using a simultaneous oxygen, nitrogen and hydrogen analyzer (ONH836, manufactured by LECO). The results are shown in Table 1.

[0107] (Preparation of Silver Powder X2) The amount of 5% by mass aqueous solution of copper (II) nitrate trihydrate was changed to 4.1 g, and a mixed solution containing silver nitrate and copper (II) nitrate trihydrate (containing 0.1% by mass of copper relative to silver) was obtained. Except for this, various operations were carried out in the same manner as in the preparation of silver powder X1 to obtain silver powder X2, which is a copper-containing silver powder. Then, various measurements were carried out using the obtained silver powder X2 in the same manner as in the preparation of silver powder X1. The results are shown in Table 1.

[0108] (Preparation of Silver Powder X3) The amount of 5% by mass aqueous solution of copper (II) nitrate trihydrate was changed to 0.2 g, and a mixed solution containing silver nitrate and copper (II) nitrate trihydrate (containing 0.005% by mass of copper relative to silver) was obtained. Except for this, various operations were carried out in the same manner as in the preparation of silver powder X1 to obtain silver powder X3, which is a copper-containing silver powder. Then, various measurements were carried out using the obtained silver powder X3 in the same manner as in the preparation of silver powder X1. The results are shown in Table 1.

[0109] (Prepare silver powder X4 to X6) Silver powder X4 was prepared which had internal voids and did not contain copper (manufactured by DOWA Electronics, "AG-4-8FD"). Silver powder X5 was prepared that had no internal voids and did not contain copper (manufactured by DOWA Electronics, "AG-4-54F"). As silver powder X6, an atomized silver-copper alloy powder (SEM average diameter 1.2 μm, manufactured by DOWA Electronics Co., Ltd.) containing 72 mass% silver and 28 mass% copper was prepared. The atomized silver-copper alloy powder is a silver-copper alloy powder produced by an atomization method. The atomized silver-copper alloy powder does not have voids inside.

[0110] Example 1 <Preparation of copper-containing silver powder> As a filler, a copper-containing silver powder made of the silver powder X1 obtained above was prepared. The following measurements were performed using the copper-containing silver powder. Note that a scanning electron microscope image of the cross section of the copper-containing silver powder according to Example 1 is shown in FIG.

[0111] [Evaluation of thermomechanical analysis] Thermomechanical analysis (TMA) of the copper-containing silver powder was carried out as follows. First, 0.3 g of copper-containing silver powder was weighed. Next, the copper-containing silver powder was put into a specified mold with a diameter of 5 mmφ, and pressed with a press machine for 1 minute under a load of 50 kg to prepare a disk-shaped measurement sample. This measurement sample was set in the sample holder of a thermomechanical analysis (TMA) device (Thermo plus EVO 2 series TMA8311), and a measurement load of 98 mN was applied by the measurement probe, and the temperature was raised from 25°C to 900°C at a heating rate of 10°C / min to measure the expansion rate and contraction rate of the measurement sample. The following evaluations were made on the measurement results from 100°C to 600°C. The expansion rate, contraction rate, and temperature at that time were recorded every second from the start of measurement (temperature rise), and a TMA curve was obtained. The obtained TMA curve was differentiated with respect to time to obtain a differential curve of the TMA curve (dTMA curve). The dTMA curve of the copper-containing silver powder of Example 1 is shown in FIG. 2. Using the above dTMA curves, the temperature and dTMA of the maximum expansion peak, the temperature and dTMA of the first contraction peak, the temperature and dTMA of the second contraction peak, and the presence or absence of meandering in the dTMA curve between 300° C. and 600° C. were confirmed. The results are shown in Table 2.

[0112] [Observation of void-containing silver particles] Using the above copper-containing silver powder, the silver particles were observed by the following method to confirm the presence or absence of voids inside the silver particles. Specifically, first, the copper-containing silver powder was placed in a resin (Epofix resin, manufactured by Struers) and a hardener (Epofix hardener, manufactured by Struers) and solidified, and the solidified resin was cut. Next, the cut surface was polished with a cross-section polisher (ArBlade5000, manufactured by Japan High-Technologies Corporation) to expose the cross section of the silver particles, and each silver particle was observed with a scanning electron microscope (JSM-IT800SHL, manufactured by JEOL Ltd.) to confirm the presence or absence of voids inside the silver particles, and the presence or absence of void-containing silver particles having voids inside the copper-containing silver powder was determined. The results are shown in Table 2. Note that more than half of the observed silver particles had voids.

[0113] [Measurement of copper content in copper-containing silver powder] The amount of copper in the copper-containing silver powder was determined by the following analytical method. The results are shown in Table 2. 1) Weigh out 1 g of sample, add 15 mL of pure water and 10 mL of nitric acid (for precision analysis), and dilute to 200 mL. The mixture was heated at 30° C. for 30 minutes. 2) After allowing the sample heated in 1) to cool, the volume was adjusted to 100 mL using pure water, 5 mL of the supernatant was removed, and the volume was again adjusted to 100 mL using pure water to prepare a sample for ICP analysis. 3) The copper standard solution used to create the calibration curve was prepared by adjusting the silver concentration using 5N silver to the same level as the sample for ICP analysis. 4) ICP quantification was performed using an Aglent 5800 ICP-OES from Agilent Technologies.

[0114] [Measurement of true density] The true density of the copper-containing silver powder was measured using a dry automatic densimeter. The results are shown in Table 2. Specifically, first, a 10cc platinum crucible was filled with copper-containing silver powder, and the mass of the filled copper-containing silver powder was precisely measured.Then, using a dry automatic density meter (Micromeritics Accupypic II1340), the volume of the copper-containing silver powder was measured from the gas volume when helium gas was filled into the crucible until a constant pressure was reached, and the true density was calculated by dividing the mass of the copper-containing silver powder by the volume.

[0115] [Measurement of BET specific surface area] The BET specific surface area of ​​the copper-containing silver powder was measured by a BET specific surface area measuring device (Macsorb HM-model 1210, manufactured by MOUNTECH) using a BET single-point method with nitrogen adsorption. In the measurement of the BET specific surface area, the degassing conditions before the measurement were 60° C. and 10 minutes. The results are shown in Table 2.

[0116] [Measurement of particle size distribution] The minimum particle size of the copper-containing silver powder based on volume (D MIN ), cumulative 10% particle diameter (D10 ), cumulative 50% particle diameter (D 50 ), cumulative 90% particle diameter (D 90 ), and cumulative 95% particle size (D 95 ), and the cumulative 100% (i.e., maximum particle) particle diameter (D MAX ) was measured by the following method. The results are shown in Table 2. 0.1 g of copper-containing silver powder was added to 40 mL of isopropyl alcohol (IPA) and dispersed for 2 minutes using an ultrasonic homogenizer (device name: US-150T, manufactured by Nippon Seiki Seisakusho Co., Ltd.; 19.5 kHz, tip diameter 18 mm), and then the particle size distribution was measured using a laser diffraction / scattering type particle size distribution analyzer (Microtrac MT-3300 EXII, manufactured by Microtrack Bell Corporation).

[0117] <Preparation of conductive paste> The above copper-containing silver powder, aluminum powder (SEM average diameter: 2.0 μm) with a metallic aluminum content of 99.87 mass% and an impurity content of 0.13 mass% (iron 0.09 mass% and silicon 0.04 mass%), glass powder (containing PbO as the main component, and containing B2O3, SiO2 and other oxides) as glass frit, ethyl cellulose, Texanol, butyl carbitol acetate, tributyl citrate, 1-octanol, oleic acid, triacetin, methylphenylpolysiloxane, hydrogenated castor oil, and fatty acid amide were mixed to obtain the composition shown in Table 3 to obtain a mixture. Next, the obtained mixture was premixed under conditions of a planetary centrifugal mixer (revolution 1000 rpm) and then kneaded with a three-roll mill (manufactured by Esact) to obtain a conductive paste. The silver content in the conductive paste was 85.305 mass %, and the copper content was 0.145 mass %.

[0118] [Line resistance value] The conductive paste obtained above was used to print a straight line shape by screen printing. The straight line was designed to have a width of 12 μm and a length of 150 mm. A Microtec printer was used for printing, and printing was performed at a ski speed of 350 mm / s. A silicon substrate with a thickness of about 170 μm (for solar cells, texture formation, SiN x A wafer (already coated with a film) was used. After printing, it was dried for 5 minutes in a dryer set at 200°C, and then baked in a solar cell baking furnace (manufactured by NGK) under conditions that would result in a peak temperature of 750°C on the top surface of the wafer to produce a sample. The resistance value of the electrode after baking (the line resistance value of the conductive film) was measured with a digital multimeter (manufactured by ADC Corporation) by placing measurement terminals on both ends of the printed electrode. The results are shown in Table 2.

[0119] Example 2 Various operations and measurements were carried out in the same manner as in the examples, except that the copper-containing silver powder made of silver powder X2 was used as the filler instead of the copper-containing silver powder made of silver powder X1. The results are shown in Table 2. The dTMA curve of the copper-containing silver powder according to Example 2 is shown in FIG. The silver content in the conductive paste of Example 2 was 85.420 mass %, and the copper content was 0.030 mass %. In addition, in the observation of the void-containing silver particles, more than half of all the silver particles observed had voids.

[0120] Example 3 Various preparations and measurements were carried out in the same manner as in the examples, except that the copper-containing silver powder made of silver powder X3 was used as the filler instead of the copper-containing silver powder made of silver powder X1. The results are shown in Table 2. The dTMA curve of the copper-containing silver powder according to Example 3 is shown in FIG. The silver content in the conductive paste of Example 3 was 85.446 mass %, and the copper content was 0.004 mass %. In addition, in the observation of the void-containing silver particles, more than half of all the silver particles observed had voids.

[0121] Comparative Example 1 Various operations and measurements were carried out in the same manner as in the examples, except that the copper-containing silver powder made of silver powder X1 was replaced with silver powder made of silver powder X4 as the filler. The results are shown in Table 2. The dTMA curve of the silver powder according to Comparative Example 1 is shown in FIG.

[0122] Comparative Example 2 Various operations and measurements were carried out in the same manner as in the examples, except that a mixed silver powder consisting of silver powder X5 and silver powder X6 was used as a filler instead of the copper-containing silver powder consisting of silver powder X1. The results are shown in Table 2. The dTMA curve of the mixed silver powder according to Comparative Example 2 is shown in FIG.

[0123] [Table 1]

[0124] [Table 2]

[0125] [Table 3]

[0126] As is clear from Table 2, the copper-containing silver powder of the examples can reduce the line resistance of the conductive film. [Industrial Applicability]

[0127] According to the present invention, it is possible to provide a copper-containing silver powder capable of reducing the line resistance of a conductive film. Moreover, according to the present invention, it is possible to provide a conductive paste capable of reducing the line resistance of a conductive film. Moreover, according to the present invention, it is possible to provide a conductive film with reduced line resistance. Moreover, according to the present invention, a solar cell having excellent performance can be provided.

Claims

1. A copper-containing silver powder comprising: In the differential curve of the TMA curve from 100 ° C. to 600 ° C. obtained by thermomechanical analysis in which the copper-containing silver powder is heated at a heating rate of 10 ° C. / min, and a first contraction peak at a temperature lower than the expansion peak and having a dTMA of -0.10% / min or less; The copper-containing silver powder has a copper content of 10 ppm or more and 10,000 ppm or less.

2. The copper-containing silver powder according to claim 1, wherein the differential curve has a second shrinkage peak with a dTMA of -0.30% / min or less between the temperature of the expansion peak and 300°C.

3. 3. The copper-containing silver powder according to claim 1, wherein the differential curve between 300°C and 600°C is meandering.

4. A conductive paste comprising the copper-containing silver powder according to claim 1 or 2, aluminum, and a solvent.

5. A conductive film formed by using the conductive paste according to claim 4.

6. A solar cell comprising the conductive film according to claim 5 .

Citation Information

Patent Citations

  • Preparation method of copper-silver composite powder

    CN102161104A

  • Method for simply preparing silver-copper bimetallic nanoparticles

    CN116060631A

  • Reaction kettle for materials

    CN211886796U

  • Resistance meter for detecting conductive slurry

    CN218917264U

  • Thermosetting conductive paste composition

    JP2011100573A